﻿Phylogenetic analyses and morphological characters reveal two new species of Ganoderma from Yunnan province, China - Jun He (Pensoft Publishers, 2021)
Ganoderma dianzhongense sp. nov. and G. esculentum sp. nov. are proposed as two new species based on both phenotypic and genotypic evidences. Ganoderma dianzhongense is characterized by the stipitate basidiomata, laccate and oxblood red pileus, gray white pore surface, duplex context and broadly ellipsoid basidiospores (9.0–12.5 × 6.5–9.0 μm) with coarse interwall pillars. Ganoderma esculentum is characterized by its basidiomata with slender stipe, white pore surface, homogeneous pileus context, and slightly truncate, narrow basidiospores (8.0–12.5 × 5.0–8.0 µm). Phylogenetic analyses were carried out based on the internal transcribed spacer (ITS), translation elongation factor 1-α (TEF1-α) and the second subunit of RNA polymerase II (RPB2) sequence data. The illustrations and descriptions for the new taxa are provided.